2016
DOI: 10.3892/mmr.2016.5136
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown by shRNA identifies SLC44A5 as a potential therapeutic target in hepatocellular carcinoma

Abstract: Abstract. Hepatocellular carcinoma (HCC) has been ranked the second leading cause of cancer-associated mortality in China and the third leading cause of cancer-associated mortality worldwide. A number of previous studies investigating SLC44A5 have revealed important biological insight and disease-specific functions. Therefore, the present study investigated the expression of SLC44A5 in HCC tissues and cell lines, and assessed the effect of SLC44A5 on the viability, cell cycle, apoptosis and invasion of HCC cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Our results are in accordance with data reported in the literature concerning the upregulation/overexpression of SLC genes in HCC, including SLC44A5 and SLC26A6 [38,40], and the downregulated expression of SLC38A4 and SLC22A1 [41,43]. A recent study evidenced SLC26A6 as a novel oncogene in HCC [147].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in accordance with data reported in the literature concerning the upregulation/overexpression of SLC genes in HCC, including SLC44A5 and SLC26A6 [38,40], and the downregulated expression of SLC38A4 and SLC22A1 [41,43]. A recent study evidenced SLC26A6 as a novel oncogene in HCC [147].…”
Section: Discussionsupporting
confidence: 93%
“…SLC44A5 is an intermediate-affinity choline transporter; high expression of SLC44A5 demonstrates its important role in the development and progression of HCC [38]. • SLC26A6 belongs to an anion transporter family [39].…”
mentioning
confidence: 99%
“…It has previously been shown that tea consumption is associated with a lower risk of developing cancer (19,31). In our regional analysis, five cancer-associated genes were differentially methylated with tea consumption in women: THBS2, which has been shown to function as a potent inhibitor of tumour growth (41) and angiogenesis (42); TSPAN32, which is located within an important tumour suppressor region (43); CTBP1, which is involved in promoting the carcinogenesis of human glioma (44); SLC44A5, a potential therapeutic target in hepatocellular carcinoma (45) and CLIC1 that is known to be overexpressed in malignant tumours (46,47) (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Promoter and enhancer regions of other genes expressed in B-cells and with known immune regulatory function and/or involvement in B-cell malignancies (SLC44A5 62,63 , FCRL3 [64][65][66][67] , SELL, TNIP2 68,69 , TRIM13 70,71,72(p13) ) were also affected by kataegis.…”
Section: Compared To the Paired Pb-cll Tissue-rs Is Characterized By Increased Mutational Burdenmentioning
confidence: 99%